An analysis of the potential of cumarin and its use as a natural pharmaceutical (Research, Society and Development, 2022)
The objective of this study was to analyze the wide variety of attributes present in coumarin, an abundant plant in the region. Amburana cearensis, popularly known as cumaru or imburana-de-cheiro, is a tree of economic importance, typical of the North and Northeast region, where it is used in several areas, such as in carpentry, perfumery, and for various pharmaceutical purposes. The Cumarins have been studied since the nineteenth century, and have shown the ability to interact, prevent and treat diseases. The Cumaru barks and seeds have been used in folk medicine and are attributed therapeutic properties such as anti-inflammatory, antispasmodic, and emmenagogue, being mainly used in respiratory tract ailments including laryngotracheal-bronchitis cough and as an expectorant. The bark of the stem and the seeds are employed in home medicine, used in the form of lick or tea, in the treatment of colds, bronchitis, flu, and asthma. The seeds are also used in the form of decoct and infusion as a remedy against muscle spasms (antispasmodic) and to treat rheumatic diseases. Given the proposed theme, it is expected that, utilizing the scientific productions that will be used to carry out this study, we can show how the use of the Amburana cearensis plant and its medicinal benefits occurs.